Influence of sexual dimorphism on stable isotopes and trace element concentrations in the greater hooked squid Moroteuthopsis ingens from New Zealand waters. (July 2020) - Lischka, A.; Braid, H.; Cherel, Y.; Bolstad, K.; Lacoue-Labarthe, T.; Bustamante, P.
Abstract: The Chatham Rise, one of the highest offshore-primary production regions in New Zealand waters, hosts a great abundance and diversity of deep-sea cephalopods including the greater hooked squid, Moroteuthopsis ingens . Stable isotope ratios of carbon ( δ 13 C) and nitrogen ( δ 15 N) and trace element concentrations (Ag, As, Cd, Co, Cr, Cu, Fe, Hg, Ni, Pb, Se, V, and Zn) were assessed in female and male specimens of different size classes (89–563 mm mantle length). Values of δ 13 C and δ 15 N were overall higher in females and δ 13 C was further influenced by size and sex. Both muscular mantle (the largest fraction of the total body mass) and digestive gland (the known main storage organ for Ag, Cd, Cu and Zn in many cephalopods) tissues were analysed. Higher levels of Cd were observed in males than in females. A positive effect was found between size and Hg concentrations, which could be related to the ontogenetic descent of larger specimens into deeper waters, where they are exposed to higher Hg concentrations, and/or dietary shifts toward Hg-enriched prey with increasing size. This study provides trace element data for this abundant and ecologically important species, and further reveals higher trace element concentrations (especially Hg) in M. ingens from the Chatham Rise, compared to specimens from the sub-Antarctic zone. Highlights: Ag, Cd, Cu, Fe, Pb were highest in the digestive gland compared to mantle. Ag and Hg concentrations showed a positive correlation with size. Cd concentrations varied between the sexes (highest in large females). Stable isotope values support an ontogenetic shift in habitat. Results suggest M. ingens is a vector for Cd and Hg in NZ pelagic predators.